ANALISIS ESTETIS TARI DRIASMARA - Dwiyasmono, Dwiyasmono; Maryono, Maryono (Institut Seni Indonesia Surakarta, 2013)
The dance Driasmara is a pasihan dance in traditional Surakarta style and a developmentof previous pasihan dances, including Karonsih, Lambangsih, Endah, and Enggar-enggar. Thisdance has a variety of moods for creating dramatic effect through its treatment of the movements,vocal melody, dance steps, levels, and musical accompaniment, so that it is interesting to analyzeits aesthetical formation. In order to discover the aesthetical formation of the dance Driasmara,tools for aesthetical analysis are required, including the concepts of wiraga, wirama, wirasa, andhasta sawanda as well as the concept of dramatic design. It is hoped that this study will bebeneficial for the development of the life of the arts, in particular aspects of aesthetical analysis.